Umedecimento e substratos para germinação de sementes de repolho - De Azeredo, Gilvaneide Alves; Da Silva E Silva, Breno Marques [UNESP]; Sader, Rubens [UNESP]; Pontes, Matos Valderez (FapUNIFESP (SciELO), 2010)
The availability of water for seeds is closely related to their germination, since hydration is a limiting factor for their metabolic processes. Therefore, in tests carried out in laboratory, substrate must be sufficiently moistened, in order to assure both the embryo growth and seedling formation. This research was carried out to evaluate the influence of different quantities of water, in different substrates, for cabbage (Brassica oleracea var. capitata) seeds germination. The seeds, processed with Thiran 0.1%, were obtained in shops located in Jaboticabal, São Paulo State, Brazil. Germination tests were made in germitest rolled paper towel substrates, between and on draft paper, moistened with quantities of water equivalent to 1.0; 1.5; 2.0; 2.5; 3.0; 3.5; and 4.0 times the dry substrate weight. For each treatment, four repetitions of 50 seeds were used. The seeds were kept in a germinator, at an alternate temperature of 20-30°C, without further addition of water to the substrate. The evaluations were made on the fifth and tenth days after the experiment preparation. The results obtained revealed that the quantities of water ranging from 1.5 to 2.5 times the paper weight were favorable for seeds germination, mainly in the substrate on and between the paper, while water levels above 3.0 times the substrate weight were harmful for cabbage seeds germination in the rolled paper towel substrates and between the paper.
Substrates and moisture levels in the germination of cabbage seeds
Keywords: Brassica oleracea var. capitata; Germination test; Quantity of water; Seed analysis